Catheter inversion during cavotricuspid isthmus catheter ablation: The new shaft visualization catheter reduces fluoroscopy use. Issue 5 (11th July 2021) - Santoro, Amato; Baiocchi, Claudia; Sisti, Nicolò; Zacà, Valerio; Pondrelli, Carlo Renato; Falciani, Francesca; Lamberti, Filippo
Abstract: Aims: Catheter ablation (CA) is the choice therapy of cavotricuspid isthmus (CTI) atrial flutter. The aim of this study was to describe our approach to improve the CTI ablation using a zero‐fluoroscopy (ZF). The procedural difficulties could be related to anatomical characteristics of the CTI. Methods: One hundred eighty‐eight patients that performed CA of CTI were retrospectively and consecutively evaluated between 2017 and 2019. The studied population was divided into two groups. Eighty‐eight patients who were undergone CA using ablation catheter without shaft visualization catheter (NSV) were Group 1. One hundred patients were undergone CA using ablation catheter with a shaft visualization (SV); they were Group 2. The catheter was looped at the Eustachian ridge after 200 seconds of radiofrequencies (RF) without elimination of local electrogram. Results: A conduction line block of CTI was obtained in all patients of Group 2 using a ZF approach. In 16 patients of Group 1, the catheter inversion was obtained using fluoroscopy to avoid damages during its loop. In Group 2, a complete CTI block was obtained with a catheter inversion approach in ten patients without fluoroscopy, visualizing the shaft and the tip of the ablation catheter on the electroanatomic (EAM) map. In the overall population studied the use of SV had a linear correlation with the ZF approach ( r  = .629; P  < .001). The duration of RF was lower in Group 2 than in Group 1 (Group 1: 27.8 ± 6.3 vs Group 2: 15.6 ± 7.2 minutes; P  < .01). The procedure time between two groups was lower in Group 2 than in Group 1 (Group 1: 58.4 ± 22.4 vs Group 2: 42.2 ± 15.7 minutes; P  < .01). No differences between two groups were documented regarding success and complications. Conclusions: The visualization of the shaft's catheter on the EAM permitted the catheter inversion safely in order to overcome some complex CTI anatomy and obtain bidirectional block. The SV reduced procedure time, RF applications and fluoroscopy exposition during CTI ablation. Abstract : A zero‐fluoroscopy catheter ablation (CA) of atrial flutter is safe and feasible. The use of ablation catheter with shaft visualization could improve the reproducibility of a successful zero‐fluoroscopy CA.